Whole-genome sequencing, de novo assembly and comparative analyses of Manis Javanica and Manis Pentadactyla / Ranjeev Hari - Ranjeev, Hari (2017)
Pangolins are unique mammals with scales over most of their body and they have no teeth, have poor vision, and an acute olfactory system. Pangolins comprise the only placental order (Pholidota) whose genomes have not been completely sequenced. The living Pholidotans are comprised of four Asian (Manis javanica, Manis pentadatyla, Manis culioensis, Manis. crassicaudata) and four African (Manis temmincki, Manis gigantae, Manis tricuspis, Manis tetradactlya) species. In this study, I sequenced and assembled the first reference genome of the Malayan pangolin (M. javanica), which is a critically endangered species from Malaysia and compared it with the closely related Chinese pangolin (M. pentadactyla) from Taiwan. Using the MAKER annotation pipeline, I identified 23,446 and 20,298 protein-coding genes in the M. javanica and M. pentadactyla genomes respectively. Strikingly, pangolins have a non-canonical repeat layout compared to closely related Carnivorans. Pangolins lack tRNA-SINES and have short mean intron length (likely due to the loss of a tRNA-SINE family) compared to other mammals, which may be associated to an inherent metabolic adaptation in the pangolins. Furthermore, ancient population history modelling showed the dwindling population of endangered pangolins, providing important insights for future conservation efforts. The results showed that long-term population decline predated recent declines which highlights the urgency to stunt such trends by introducing tighter regulations and accelerating conservation efforts of these endangered pangolins. I also found the presence of Burkholderia fungorum in the supposed sterile pangolin tissues of cerebrum, cerebellum, lung and blood, suggesting that this bacterium has capability to colonise pangolins. In addition to the nuclear genomes of pangolins, I also assembled the associated reference mitogenomes of M. javanica and M. pentadactyla. Phylogenetic trees based on the newly assembled mitogenomes confirmed that the pangolin that were sequenced in this study were indeed M. javanica. Furthermore, I have also identified and annotated 7,422 expressed long non-coding RNA (lncRNA) in pangolins. Overall, the pangolin whole-genome assemblies, mitogenomes, list of genes and lncRNAs will serve as important resources to the research community in the future in areas such as conservation efforts, molecular biology, genetics and evolutionary biology.